2018
DOI: 10.1016/j.cell.2018.08.038
|View full text |Cite
|
Sign up to set email alerts
|

Transaminase Inhibition by 2-Hydroxyglutarate Impairs Glutamate Biosynthesis and Redox Homeostasis in Glioma

Abstract: IDH1 mutations are common in low-grade gliomas and secondary glioblastomas and cause overproduction of (R)-2HG. (R)-2HG modulates the activity of many enzymes, including some that are linked to transformation and some that are probably bystanders. Although prior work on (R)-2HG targets focused on 2OG-dependent dioxygenases, we found that (R)-2HG potently inhibits the 2OG-dependent transaminases BCAT1 and BCAT2, likely as a bystander effect, thereby decreasing glutamate levels and increasing dependence on gluta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
266
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(291 citation statements)
references
References 57 publications
6
266
1
2
Order By: Relevance
“…The epigenetic alterations induced by IDH mutation in vitro are partially reversible, contribute to transcriptional remodeling and deposition of histone modifications at specific genomic loci, promote the emergence of a CD24 + stem-like population, and contribute to increased genomic instability (Turcan et al 2018). In addition to the more Galli et al 2004;Singh et al 2004;Bidlingmaier et al 2008;Gilbert and Ross 2009;Son et al 2009;Wan et al 2010 In well-known inhibition of histone and DNA demethylases, the mutant IDH oncometabolite 2-hydroxyglutarate (2-HG) establishes a synthetic dependency on glutaminase through inhibiting branched-chain amino acid metabolism (McBrayer et al 2018). In IDH wild-type glioblastomas, global methylation profiling through reduced representation bisulfite sequencing (RRBS) from primary surgical specimens infers glioblastoma transcriptional subtypes, documents intratumoral heterogeneity of tumor cells as well as immune infiltrates, and detects subtype changes between primary and recurrent tumors (Klughammer et al 2018).…”
Section: Glioma Stem Cell Epigenetics: Interface Between Environmentmentioning
confidence: 99%
“…The epigenetic alterations induced by IDH mutation in vitro are partially reversible, contribute to transcriptional remodeling and deposition of histone modifications at specific genomic loci, promote the emergence of a CD24 + stem-like population, and contribute to increased genomic instability (Turcan et al 2018). In addition to the more Galli et al 2004;Singh et al 2004;Bidlingmaier et al 2008;Gilbert and Ross 2009;Son et al 2009;Wan et al 2010 In well-known inhibition of histone and DNA demethylases, the mutant IDH oncometabolite 2-hydroxyglutarate (2-HG) establishes a synthetic dependency on glutaminase through inhibiting branched-chain amino acid metabolism (McBrayer et al 2018). In IDH wild-type glioblastomas, global methylation profiling through reduced representation bisulfite sequencing (RRBS) from primary surgical specimens infers glioblastoma transcriptional subtypes, documents intratumoral heterogeneity of tumor cells as well as immune infiltrates, and detects subtype changes between primary and recurrent tumors (Klughammer et al 2018).…”
Section: Glioma Stem Cell Epigenetics: Interface Between Environmentmentioning
confidence: 99%
“…The IDH mutant gliomas (patient-derived glioma stem-like cells and human oligodendroglioma cell line grown in vitro and in xenografts) were also shown as being specifically sensitive to GLS inhibition by CB-839. The glutamate deficiency due to BCAA transaminases inhibition by D2HG was potentiated by the GA inhibition and resulted in lowering of the GSH level, which rendered the gliomas susceptible to experimental treatment, including oxidative stress and radiation [81].…”
Section: Modulation Of Gasmentioning
confidence: 99%
“…Subsequently, Glu is either metabolized to the TCA cycle intermediate alphaketoglutarate (αKG), which is then used as a nitrogendonor during the synthesis of several nonessential amino acids, or mediates redox homeostasis by increasing the production of the antioxidant glutathione (GSH). Since several oncogenes regulate GLS expression and many studies have shown that cancer cells are GLSdependent 3,9,10 , GLS inhibitors (GLSi) (have been designed and evaluated in preclinical and clinical trials for brain tumors (trial ID: NCI-2018-00876) [11][12][13] . The specific and orally bioavailable small molecule inhibitor CB839 has been shown to effectively reduce viability, chemosensitivity, and induce apoptosis in several tumor entities including breast, ovarian, prostate, and lung cancer [14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%